Diseño de un sistema control autónomo contraincendios para laboratorios y biblioteca de la universidad Antonio Nariño, sede Villavicencio (2021)
Currently the Antonio Nariño University Villavicencio campus does not have a fire protection system that protects the university community and infrastructure, it is sought through the analysis of the existing risk and danger matrix, to design an autonomous fire control system for laboratories and library of the campus, being the areas most vulnerable to a conflagration, this in accordance with the requirements of the NSR-10 standard, limiting itself to the design according to the technical requirements of the hydraulic network, programming of the automatic control system and one-line diagram of the power system , providing well-being to the UAN community by adjusting the infrastructure to current regulations, remaining at the forefront with regard to the universities in the region that have all these protective equipment.